Bridging the gap between user requirements and user interface design / Bainaiah Misiran - Misiran, Bainaiah (2005)
The important aspect of future software engineering techniques will be the ability to seamlessly move from analysis to design. There are many welldefined processes for evaluating usability of an interface once it has been designed. One step in design process, however, has been oddly neglected: the ways to transform user requirements into initial interface design. For that reason, this study is carried out in order to reach two main things; identifying the existing problems in transforming user requirements into user interface design and from this, identify the ways to transform information gathered about user requirements into the user interface. To achieve it, researcher distributed questionnaires to IT companies as primary data to get a data. The results indicate that there are many problems during the transformation and some of them know how to solve the problems but they also don't know how to overcome the problems. Mostly the problems identified are caused from a poor user requirements and the user involvement in this transition is important. Hopefully with conducting this study it can help to improve the effectiveness in software development process.